GEC-ESTRO ACROP recommendations for head & neck brachytherapy in squamous cell carcinomas: 1st update – Improvement by cross sectional imaging based treatment planning and stepping source technology. Issue 2 (February 2017) - Kovács, György; Martinez-Monge, Rafael; Budrukkar, Ashwini; Guinot, Jose Luis; Johansson, Bengt; Strnad, Vratislav; Skowronek, Janusz; Rovirosa, Angeles; Siebert, Frank-André; ,
Abstract: The Head and Neck Working Group of the GEC-ESTRO (Groupe Européen de Curiethérapie – European Society for Therapeutic Radiology and Oncology) published in 2009 the consensus recommendations for low-dose rate, pulsed-dose rate and high-dose rate brachytherapy in head & neck cancers. The use of brachytherapy in combination with external beam radiotherapy and/or surgery was also covered as well as the use of brachytherapy in previously irradiated patients. Given the developments in the field, these recommendations needed to be updated to reflect up-to-date knowledge. The present update does not repeat basic knowledge which was published in the first recommendation but covers in a general part developments in (1) dose and fractionation, (2) aspects of treatment selection for brachytherapy alone versus combined BT + EBRT and (3) quality assurance issues. Detailed expert committee opinion intends to help the clinical practice in lip-, oral cavity-, oropharynx-, nasopharynx-, and superficial cancers. Different aspects of adjuvant treatment techniques and their results are discussed, as well the possibilities of salvage brachytherapy applications.